Low rate of azole resistance in cases of avian aspergillosis in Germany. (4th June 2020) - Barber, Amelia E; Scheufen, Sandra; Walther, Grit; Kurzai, Oliver; Schmidt, Volker
Abstract: Aspergillosis is the most common fungal disease of the avian respiratory tract. Due to delayed diagnosis and treatment failure, the outcome of these infections is often poor. We investigate 159 cases of avian aspergillosis among captive birds in Germany to define clinical features as well as the frequency of in vitro triazole resistance. Adult birds were more likely to present with clinical signs compared to juvenile birds, and dyspnoea was the most common clinical sign, present in 53% of birds. Molecular species identification indicated that all infections were caused by Aspergillus fumigatus . Only one of 159 independent isolates was azole resistant.